Effects of psychological interventions on high sports performance: A systematic review - Reyes-Bossio, Mario; Corcuera-Bustamante, Santiago; Veliz-Salinas, Giancarlo; Villas Boas Junior, Marcelo; Delgado-Campusano, Mariel; Brocca-Alvarado, Paul; Caycho-Rodríguez, Tomás; Casas-Apayco, Leslie; Tutte-Vallarino, Veronica; Carbajal-León, Carlos; Brandão, Regina (Frontiers in Psychology, 2022)
Intervention programs in sports psychology aid to modify the thoughts and behaviors of athletes in order to improve their performance in sports settings. For high-performance athletes, these interventions are very relevant, given that they constantly face pressure towards obtaining sporting achievements. This systematic review aims to analyze the scientific articles between 2010-2020 that evaluated the effect of psychological interventions on high-performance athletes. In the search procedure, nine studies were selected, the most studied variables were psychological skills, psychological flexibility and stress. 44% of the interventions were designed by the research authors themselves, while the remaining 56% were replicated programs, which already had scientific evidence. In conclusion, psychological interventions have a positive impact on sports performance. This review allows sports institutions and professionals to have more knowledge and resources at their disposal to implement these types of programs in their sports planning.